The HDAC and PI3K dual inhibitor CUDC-907 synergistically enhances the antileukemic activity of venetoclax in preclinical models of acute myeloid leukemia - Xinyu Li; Yongwei Su; Katie Hege; Gerard Madlambayan; Holly Edwards; Tristan Knight; Lisa Polin; Juiwanna Kushner; Sijana H. Dzinic; Kathryn White; Jay Yang; Regan Miller; et al. (Haematologica, 2020)
Venetoclax is a promising agent in the treatment of acute myeloid leukemia, though its antileukemic activity is limited to combination therapies. Mcl-1 downregulation, Bim upregulation, and DNA damage have been identified as potential ways to enhance venetoclax activity. In this study, we combine venetoclax with the dual PI3K and histone deacetylase inhibitor CUDC-907, which can downregulate Mcl-1, upregulate Bim, and induce DNA damage, as well as downregulate c-Myc. We establish that CUDC-907 and venetoclax synergistically induce apoptosis in acute myeloid leukemia cell lines and primary acute myeloid leukemia patient samples ex vivo. CUDC-907 downregulates CHK1, Wee1, RRM1, and c-Myc, which were found to play a role in venetoclax-induced apoptosis. Interestingly, we found that venetoclax treatment enhances CUDC-907-induced DNA damage potentially through inhibition of DNA repair. In vivo results show that CUDC-907 enhances venetoclax efficacy in an acute myeloid leukemia cell line derived xenograft mouse model, supporting the development of CUDC-907 in combination with venetoclax for the treatment of acute myeloid leukemia.